Theoretical investigation of superconductivity mechanism in the filled skutterudites YRu4P12, YOs4P12, LaOs1P12 and LaOs4As12. (July 2019) - Uzunok, H.Y.; Tütüncü, H.M.; Karaca, Ertuǧrul; Srivastava, G.P.
Abstract: We have searched the structural, electronic, phonon and electron-phonon interaction properties of the filled skutterudites YRu4 P12, YOs4 P12, LaOs4 P12 and LaOs4 As12 by utilizing the generalized gradient approximation of the density functional theory. A critical assessment of their electronic density of states (DOS) indicates that the partial DOS of transition metal and pnictogen are considerably present in the energy range below and above the Fermi level but the contribution of the rattling atom (Y or La) to the occupied bands is negligible. The calculated zone-center phonon frequencies of LaOs4 As12 compare very well with previous theoretical results. Our electron-phonon calculations suggest that all the studied skutterudites are phonon-mediated conventional superconductors since phonon scattering of electrons plays main role in the transition from the normal state to the superconducting state. A detailed analysis of the Eliashberg spectral function reveals that the contribution of the rattling atom-related vibrations to the electron-phonon interaction properties is moderate. The superconducting critical temperature is found to be 7.73, 2.67, 2.03 and 3.2 for YRu4 P12, YOs4 P12, LaOs4 P12 and LaOs4 As12, respectively. These values show a good agreement with their experimentally reported values of 8.5, 2.8, 2.0 and 3.2 K. Graphical abstract: Image 1 Highlights: The structural and electronic properties of the studied filled skutterudites are the-oretically investigated. Phonons and electron-phonon interaction in these filled skutterudites are studied using a linear response theory. Our calculations suggest that all the studied skutterudites are phonon-mediated BCS-type superconductors. We found that the contribution of the rattling modes to the electron-phonon in-teraction properties is moderate. The calculated Tc values are in a good agreement with experimentally reported values the studied materials.